A Comprehensive Description of Hypoxia-inducible Factor 2α Inhibitors as Anticancer Agents: A Mini-review - Lu, Hongyuan; Zhu, Yan; Liu, Wenwu; Yan, Yuanyuan; Jiang, Xiaowen; Wang, Qinbiao; Zhao, Yanyun; He, Miao; Wei, Minjie (Current Medicinal Chemistry, 2023)
Targeting the tumor microenvironment is a promising strategy to prevent metastasis, overcome acquired drug resistance, and improve the therapeutic effect. Hypoxia is one of the characteristics of the tumor microenvironment, which is mainly regulated by hypoxia-inducible factors. Hypoxia-inducible factors (HIFs) including HIF-1α, HIF-2α, and HIF-3α, of which HIF-2α has assumed a more important role in tumor hypoxia environment. It has been demonstrated that HIF-2α plays an important role in tumor diseases, including renal cell carcinoma, breast cancer, non-small cell lung cancer, and gastric cancer, among others. Therefore, targeting HIF-2α has become one of the important strategies for treating cancers. HIF-2α inhibitors can be divided into two categories: specific inhibitors and non-specific inhibitors. The former includes synthetic monomer compounds and traditional Chinese medicine extracts. In this review, we summarized, classified, and discussed current research on the structure, structure-activity relationship (SAR), and pharmacology of HIF-2α inhibitors, which is helpful to the rational design of effective drugs for various types of malignant tumors.
Keywords: hypoxia